JURIDICAL REVIEW OF THE TRANSFER OF LAND RIGHTS ORIGINATING FROM A DEBT AND CREDIT AGREEMENT : STUDY OF DECISION NUMBER 73/PDT/2018/PT SMG - Kristanto, Adek Bagus; Novianto, Widodo Tresno; Purwadi , Hari (PT. Altin Riset Publishing, 2025)
The transfer of land rights originating from a debt agreement is a legal phenomenon that often occurs in society. The purpose of this study is to understand the legal actions in which the burdening of rights changes into a transfer of rights and to determine the legal consequences of the annulment of the transfer of rights based on court decision number 73/PDT/2018/PT SMG. The method used in this research is normative juridical law. The result of this research is that the annulment of the transfer of rights provides an important lesson that every transfer of rights must be carried out by adhering to valid legal procedures to avoid legal harm to the parties involved and to ensure legal certainty in the national land administration system.